Food preparation for carrot-based cattle (Daucus carota L.) using solid state fermentation for an eco-efficient alternative - Fonseca-López, Diana; Saavedra-Montañéz, Gabriel; Rodríguez-Molano, Carlos Eduardo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Livestock feeding must use sustainable strategies because of the pressure exerted on natural resources seen with concentrated feed; solid state fermentation (FES) allows for the design of foods with less environmental impact because of the action of efficient microorganisms that enrich the residues of crops and flours with a low nutritional value. The objective of this research was to create a carrot-based FES (Daucus carota L.) food in combination with other ingredients as an alternative for cattle feed; for this, three solid-state fermented products (72 hours) were obtained with the inclusion of carrot (FES 1 [control], FES 2 [without repel of wheat] and FES 3 [without coffee husk]). The pH variation was evaluated during the fermentation process, and a compositional analysis and microbiological analysis of the diets were performed. A 4-fold increase in the initial protein value (BP) at 48 hours was obtained, from 4.34 to 19% (FES 1), 17.4% (FES 2) and 14.4% (FES 3) (P≤0.05). The highest growth of total mesophiles at 24 hours was observed with 69×10-3 UFC/g (FES 1), 120×10-3 UFC/g (FES 2) and 45×10-3 UFC/g (FES 3) (P≤0,05); the pH dropped at 96 hours of fermentation of 5.9 (FES 1) (FES 1), 6 (FES 2) and 6.05 (FES 3) at 4.89 (FES 1), 4.91 (FES 2) and 5 (FES 1) FES 3) (P≤0.05), respectively. It was concluded that, with the FES biotechnology, it is possible to use carrot mixed with other raw materials to obtain eco-efficient cattle feed.